Possibilities of the Cultural-Historical Approach to Gender Issues - Alexander Sh. Tkhostov; Sergey K. Kumchenko (Lomonosov Moscow State University, 2024)
Background. The relevance of gender issues is associated with discussions outside the scientific field, while in the science itself, the popularity of gender studies is increasing every year. Objectives. The present article aims at the application of the conceptual mechanism of the cultural-historical approach to gender issues. Methods. Abstraction, analysis and synthesis of literary data, comparison of theoretical models, and generalization were used. Results. Sex as a biological entity is divided into an innate "natural" category and a gender as a culturological one. A number of examples demonstrate the non-identity of sex and gender as well as variants of their combination and interaction. It is proposed to disidentify gender and gender identity as a psychological category. The latter is understood as an analogue of the higher mental function which forms intravitally under specific social conditions, it is mediated by gender signs (appearance, manners, norms, preferences, values, taboos, etc.) and is possible to self-regulate. In the meantime, the limitations in mastering one's own behaviour are emphasized, since the origin of the gender identity is connected to the biological parameters of sex, inconsistency of gender norms and their wide field of influence. Here the field of cultural pathology in the sphere of gender identity and intersex interaction reveals itself. Conclusions. The cultural-historical approach is seen to be heuristic in the multifactorial understanding of gender issues which include biological, cultural, psychological, and ontogenetic aspects.